2008
DOI: 10.1016/j.molcel.2007.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SUMO-Dependent Chromatin-Associated Transcriptional Repression Components by a Genome-wide RNAi Screen

Abstract: SUMO modification of many transcription factors is linked to transcriptional repression. The molecular mechanisms by which SUMO attachment represses transcription are largely unknown. Here we report a genome-wide RNA interference screen in Drosophila melanogaster cells for components regulating and mediating SUMO-dependent transcriptional repression. Analysis of >21,000 double-stranded RNAs (dsRNAs) identified 120 genes whose dsRNA-mediated knockdowns impaired SUMO-dependent transcriptional repression. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 55 publications
2
126
0
2
Order By: Relevance
“…The accumulation of ubiquitylated H2A(X) and sumoylated chromatin components that occur downstream of γH2AX formation have been associated with transcriptional silencing in different contexts. 117,[125][126][127][128] Therefore, it is tempting to speculate that γH2AX formation and transcriptional silencing of the XY chromosome pair in meiosis evolved as a specialization of a general silencing mechanism that prevents ongoing RNA transcription from a damaged template when DSB repair is ongoing or blocked. Functional analyses of the initiating events in MSUC and MSCI will reveal the complex interplay between meiotic DSB repair, chromosome synapsis and silencing of chromatin that lacks a pairing partner.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ubiquitylated H2A(X) and sumoylated chromatin components that occur downstream of γH2AX formation have been associated with transcriptional silencing in different contexts. 117,[125][126][127][128] Therefore, it is tempting to speculate that γH2AX formation and transcriptional silencing of the XY chromosome pair in meiosis evolved as a specialization of a general silencing mechanism that prevents ongoing RNA transcription from a damaged template when DSB repair is ongoing or blocked. Functional analyses of the initiating events in MSUC and MSCI will reveal the complex interplay between meiotic DSB repair, chromosome synapsis and silencing of chromatin that lacks a pairing partner.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast and animals, SUMO modification is involved in various biological processes including chromatin organization and transcriptional regulation (Shin et al, 2005;Shiio and Eisenman, 2003;Nathan et al, 2006;Cubeñas-Potts and Matunis, 2013). Noncovalent interaction of SUMO proteins with chromatin-associated proteins is also required for SUMO-dependent transcriptional regulation (Stielow et al, 2008;Ouyang et al, 2009;Cubeñas-Potts and Matunis, 2013). In Arabidopsis, mass spectrometric analysis of purified sumoylated proteins demonstrated that many SUMO substrates are involved in chromatin structure regulation, transcription, and RNA metabolism (Budhiraja et al, 2009;Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SUMOylation is a covalent post-translational modification, whereby SUMO is attached by an iso-peptide linkage to lysine(s) residue in the target protein (Bayer et al, 1998;Johnson, 2004;Mukhopadhyay and Riezman, 2007). Recent studies have shown that SUMOylation of specific chromatinassociated factors regulates gene expression by altering chromatin architecture, which results in localized heterochromatinization and inability of the transcription machinery to interact at specific chromatin sites (Stielow et al, 2008a;Stielow et al, 2008b;Uchimura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%